A PENGARUH SISTEM INFORMASI MANAJEMEN RUMAH SAKIT (SIMRS) DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN DI RUMAH SAKIT PARU RESPIRA DINAS KESEHATAN DAERAH ISTIMEWA YOGYAKARTA - Muhammad Isnaini Fathoni; fahlefi, wilis; Hadan Widi Astuti; Herman Wahyu Dwi Maelana (ALBAMA: JURNAL BISNIS ADMINISTRASI DAN MANAJEMEN, 2024)
Abstract One of the success of performance is influenced by a positive work environment, adequate facilities and organizational culture. One example of facilities in hospitals to support employee performance is the availability of quality information systems. The purpose of this study is to determine the influence of SIMRS and organizational culture on employee performance at Lung Respira Hospital Yogyakarta. This study uses a quantitative method with a sampling technique using propability sampling. The population of this study is all employees at Respira Lung Hospital Yogyakarta as many as 121 people. The number of samples in this study is 55 people. Data collection was carried out by filling out a questionnaire using the google form application. The data analysis in this study used multivariate, bivariate, and multivariate analysis. The results showed that the SIMRS variable had no significant effect on the Employee Performance variable with a value of 0.141 > 0.05, while the Organizational Culture variable had a significant effect on the Employee Performance variable with a value of 0.001 < 0.05. Based on the determination test, it was shown that SIMRS and Organizational Culture simultaneously affected employee performance by 0.369 (36.9%) while the rest (63.1%) was influenced by other variables that were not discussed in this study. Keywords: SIMRS; Budaya Organisasi; Kinerja Karyawan